SIMULATION OF VOLCANIC ASH DISTRIBUTION WITH FALL3D (CASE STUDY : MOUNT MERAPI ERUPTION ON NOVEMBER 2010) - RITDIAWATI PARMANAH (NIM : 12809012); Pembimbing : Dr. Tri Wahyu Hadi , HANA
For air transport security, prediction of volcanic ash distribution is needed. The previous study still have shortcomings in predicting this volcanic ash distribution. The previous results of the distribution does not have compatibility with Multifunctional Transport Satellites (MTSAT) satellite images for cloudy weather conditions. This is because the previous model did not take into account the vertical velocity of the wind. Vertical velocity is closely related to the process of convection in which the cloud is formed. Therefore, to improve outcomes for ash distribution in cloudy weather, it needs a model volcanic ash distribution that takes into account the distribution of the vertical velocity. FALL3D is one model that takes into the distribution of volcanic ash vertical velocity. FALL3D requires meteorological data input from other models. It use two other meteorological data, the data from the Final Analysis (FNL) global model and data from the atau Weather Research Forecast (WRF) regional model. The results of the distribution of volcanic ash WRF using FALL3D model show the suitability with the MTSAT satellite imagery due to the WRF has sufficient horizontal and vertical resolution to predict the phenomenon of cloudy weather. While the FNL nonconformance with the MTSAT satellite imagery since FNL does not have sufficient horizontal and vertical resolution to predict the phenomenon of cloudy weather.